Visceral ischaemia and organ dysfunction after hybrid repair ofcomplex thoracoabdominal aneurysms - Biasi, L.; Tecchio, T. (Acta Biomedica Atenei Parmensis, 2011)
Background: The visceral hybrid repair of thoracoabdominal aneurysms (TAAAs) is a feasible and relatively safe alternative to traditional open repair in a cohort of patients at high surgical risk, averting the need for thoracotomy and supra-coeliac aortic cross clamping. The visceral ischaemia-reperfusion syndrome and organ dysfunction following visceral debranching is still unkown. This study investigates the relationship between visceral ischemia and multi system organ dysfunction. Patients and Methods: 18 consecutive patients undergoing elective, urgent and emergent hybrid repair of TAAAs between February 2005 and October 2007 were prospectively analyzed. Preoperative organ dysfunction and intraoperative risk factors (operating time, extent of the aneurysm, number of visceral vessels by passed) were assessed and compared with postoperative organ dysfunction (pulmonary, hepatic, renal, pancreatic and haematological disorders). Blood sampling for neutrophil CD 11b quantification was performed at baseline, on postoperative days 1, 3, 7 and before discharge. Results: Perioperative Multi System Organ Dysfunction (MSOD) was diagnosed in 22.2% of patients (n=4/18).  Three of these patients died within 30 days (16.7%, n=3/18). No relationship between preoperative organ dysfunction, blood loss, or operative time and postoperative organ dysfunction was observed. A significant correlation between the visceral retrograde revascularization and postoperative neutrophil expression in MSOD patients regardless of preoperative neutrophil baseline, TAAA extent and number of vessels by passed was present. Conclusions: Upregolation of neutrophils may be responsible for the higher incidence of MSOD and it may be an important marker predicting a severe multiple organ failure following visceral debranching in hybrid procedures.